Analytic solution to the generalized complex Duffing equation and its application in soliton theory. Issue 13 (3rd October 2021) - Salas, Alvaro H. S.
ABSTRACT: In this paper, we give the analytical solution to the generalized Duffing equation with complex coefficients subjected to an arbitrary given initial conditions. We provide the solution in terms of the famous Weierstrass elliptic function. This solution is used to obtain the flow of the dynamical system associated to Duffing equation. We illustrate the obtained results by means of applications in Soliton Theory.